PENGARUH KOMPETENSI PENGELOLA KEUANGAN, AUDIT INTERNAL DAN SISTEM PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN UNIVERSITAS HALU OLEO - Omasrianto, Omasrianto; Hasbudin, Hasbudin; Mas’ud, Arifuddin (JPEP (Jurnal Progres Ekonomi Pembangunan), 2017)
This study aimed to determine the impact of financial manager’s competence, internal audit and internal control system on the financial reports at Halu Oleo University. The study considered primary data collected using a questionnaire. Respondents of this study were 87 financial managers. The study investigated the competence of financial managers, internal audit and internal control system as independent variables, the quality of financial reports as a dependent variable.Data analysis was perfomed using regresion wich was run on the SPSS 23 and was explained using descriptive statistic and inferential statistic analysis. Result of the study showed that the competence of financial managers had not significant effect on the quality of financial report, internal audit had significant effect on the quality of financial report, and internal control system had significant effect on the quality of financial report. Keywords: Competence of Financial Managers, Internal Audit, Internal Control System, Quality of Financial Report